Metabolomic profile of arterial stiffness in aged adults. (January 2018) - Koh, Angela S; Gao, Fei; Liu, Jin; Fridianto, Kevin Timothy; Ching, Jianhong; Tan, Ru San; Wong, Jia-Ing; Chua, Serene JM; Leng, Shuang; Zhong, Liang; Keng, Bryan MH; Huang, Fei Qiong; et al.
Background: Increasing arterial stiffness is an important contributor to declining cardiovascular health in ageing. Changes in whole-body fuel metabolism could be related to alterations in arterial stiffness in ageing adults. Methods: Targeted high-performance liquid and gas chromatography mass spectrometry were used to measure 84 circulating metabolites in a group of community elderly adults ( n = 141, 58% men; mean age = 70.6 ± 11.2 years) without cardiovascular disease. In basic and adjusted models, we correlated the measured metabolites to carotid–femoral pulse wave velocity assessed by applanation tonometry. Results: Age ( β = 0.10, p < 0.0001), smoking status ( β = 1.32, p = 0.02), dyslipidemia ( β = 1.22, p = 0.01), central systolic blood pressure ( β = 0.05, p < 0.0001), central mean arterial pressure ( β = 0.04, p = 0.03) and central pulse pressure ( β = 0.05, p < 0.0001) were significantly associated with pulse wave velocity. Amino acids such as histidine, methionine and valine correlated with pulse wave velocity. In multivariable models adjusted for clinical covariates, only Factor 5, comprising the medium- and long-chain dicarboxyl and hydroxyl acylcarnitines was independently associated with pulse wave velocity ( β = 0.24, p = 0.015). Conclusion: An upstream metabolic perturbation comprising medium- and long-chain dicarboxyl and hydroxyl acylcarnitines, likely reflecting changes in cellular fatty acid oxidation, was associated with arterial stiffness among aged adults. This advances mechanistic understanding of arterial stiffness among aged adults before clinical disease.